2016
DOI: 10.4049/jimmunol.1500532
|View full text |Cite
|
Sign up to set email alerts
|

Gαi2 and Gαi3 Differentially Regulate Arrest from Flow and Chemotaxis in Mouse Neutrophils

Abstract: Leukocyte recruitment to inflammation sites progresses in a multistep cascade. Chemokines regulate multiple steps of the cascade including arrest, transmigration and chemotaxis. The most important chemokine receptor in mouse neutrophils is CXCR2, which couples through Gαi2 and Gαi3-containing heterotrimeric G proteins. Neutrophils arrest in response to CXCR2 stimulation. This is defective in Gαi2 deficient neutrophils. Here, we show that Gαi3 deficient neutrophils showed reduced transmigration but normal arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 59 publications
1
31
1
Order By: Relevance
“…Once extravasating, neutrophils interact with inflamed pericytes via two key components, namely, the CXCR2 ligand CXCL1 and the β2 integrin ligand ICAM‐1 . We therefore next tested if taxol inhibition of neutrophils interferes with chemokinetic neutrophil motility on a substrate coated with CXCL1 alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once extravasating, neutrophils interact with inflamed pericytes via two key components, namely, the CXCR2 ligand CXCL1 and the β2 integrin ligand ICAM‐1 . We therefore next tested if taxol inhibition of neutrophils interferes with chemokinetic neutrophil motility on a substrate coated with CXCL1 alone.…”
Section: Resultsmentioning
confidence: 99%
“…Experiment in C is a representative of 5. ns = nonsignificant integrin ligand ICAM-1. [36][37][38][39][40] We therefore next tested if taxol inhibition of neutrophils interferes with chemokinetic neutrophil motility on a substrate coated with CXCL1 alone. This locomotion was confirmed to be both CXCL1 and CXCR2 dependent (Supplemental Fig.…”
Section: Chemokinetic Neutrophil Motility On Immobilized Cxcl1 Is Assmentioning
confidence: 99%
“…Moreover, recently, it has has been shown to be activated by a non-GPCR dependent mechanism at the Golgi (Lo et al, 2015). Gαi3 is also activated on other subcellular membranes, like LC3-positive autophagosomes (Garcia-Marcos et al, 2011), melanosomes (Young et al, 2011) and at the plasma membrane (Thompson et al, 2007;Kuwano et al, 2016). Thus, the same signaling molecules can operate in different ways in different regulatory networks for different purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the reduction of the proinflammatory molecule CXCL1, a potent chemoattractant of neutrophils [ 28 30 ], in BAL and in the serum of COPD+Exe group could putatively lead to the reduction of neutrophil migration and activation in airways and consequently minimize the damage of chronic exposition of cigarette smoke in the lung. Moreover, it was demonstrated that polymorphonuclear cell migration after a session of physical exercise is altered due to lack of response of cell-specific membrane receptors to specific chemokines, as well as to the alteration in the polarization of these cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%